Advances in Escherichia coli Nissle 1917 as a customizable drug delivery system for disease treatment and diagnosis strategies. (February 2023) - Chen, Haojie; Lei, Pengyu; Ji, Hao; Yang, Qinsi; Peng, Bo; Ma, Jiahui; Fang, Yimeng; Qu, Linkai; Li, Hua; Wu, Wei; Jin, Libo; Sun, Da
Abstract: With the in-depth and comprehensive study of bacteria and their related ecosystems in the human body, bacterial-based drug delivery system has become an emerging biomimetic platform that can retain the innate biological functions. Benefiting from its good biocompatibility and ideal targeting ability as a biological carrier, Escherichia coli Nissle 1917 (ECN) has been focused on the treatment strategies of inflammatory bowel disease and tumor. The advantage of a bacterial carrier is that it can express exogenous protein while also acting as a natural capsule by releasing drug slowly as a result of its own colonization impact. In order to survive in harsh environments such as the digestive tract and tumor microenvironment, ECN can be modified or genetically engineered to enhance its function and host adaptability. The adoption of ECN carries or expresses drugs which are essential for accurate diagnosis and treatment. This review briefly describes the properties of ECN, the relationship between ECN and inflammation and tumor, and the strategy of using surface modification and genetic engineering to modify ECN as a delivery carrier for disease treatment. Graphical abstract: Image 1